REVIEW FOR EXTERNAL CAUSE CODING OF INJURY CASE ON MEDICAL RECORD INPATIENT OF ORTHOPEDIC SPECIALIST SURGERY IN RSKB BANJARMASIN SIAGA IN 2013 - Yuliana, Rina; Hosizah, -; Irmawan, - (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2014)
ABSTRACTBackgrounds: External cause code is a secondary code is used to encode diagnose the cause of the occurrenceof an injury outside. The code can influence health care cost and morbidity information. Most hospitals arestill not applying external cause code in the process of classification and coding of disease, including theBanjarmasin Siaga Special Surgery Hospital.Objectives: This research aim is to find external cause coding for injury case on medical record inpatient oforthopedic specialist surgery in RSKB Banjarmasin Siaga in 2013.Methods: This research used descriptive method with case study approach. The samples are 92 inpatientorthopedic specialist surgery with injury cases medical records from January to April 2013. Data collectiontechniques that had been used were observation and interviews. The research instruments are check list,interview guides, and observation guideline. This research was analyzed using univariate analysis.Results: There has been no Operational Standard Procedures of external cause coding but OperationalStandard Procedures coding and disease indexing already exist, but not yet appropriate with the implementation.Completeness of external cause diagnosis writing is 82% and 18% did not completely written. External causesinjury to the orthopedic specialist surgery cause by land transportation accidents is 43%, other transportationaccidents is 23%, fell is 20%, and other external causes is 14%. The influence factors of external cause codingare the absence of procedures for external cause coding, the lack on media used, unsuitable human resourcesthat needed, unreadable, incomplete, and unsuitable diagnosis with the rules, and the absence diagnosiscoding audit.Kata kunci: External Cause Coding, Injury, Medical Record Inpatient, Orthopedic